Decomposition of the Gender Wage Gap Using Matching: An Application for Switzerland - Dragana Djurdjevic; Sergiy Radyakin (Swiss Journal of Economics and Statistics, 2007)
We investigate the gender wage differentials for Switzerland. Using the Swiss Labour Force Survey, we apply a matching method. Compared to the Oaxaca-Blinder decomposition, this nonparametric technique does not require any estimation of wage equations and accounts for differences that can be due to differences in the support. Our results show that differences in gender supports matter in explaining wage differentials. They can be interpreted as a form of "discrimination" in wages because women face "barriers to the entry" in accessing certain individual characteristics that men achieve. Thus, accounting for these differences may be useful in terms of policy implications in promoting more equality between men and women.
Keywords: C14; J16; J71; 330; discrimination; gender wage gap; matching